Ohaaki geothermal system: Refinement of a conceptual reservoir model. (January 2016) - Mroczek, E.K.; Milicich, S.D.; Bixley, P.F.; Sepulveda, F.; Bertrand, E.A.; Soengkono, S.; Rae, A.J.
Highlights: Geothermal drilling began in 1960s, with >70 wells drilled for various purposes. High temperature resource hosted in a volcaniclastic sequence over greywacke basement. MT identifies a sub-vertical low resistivity anomaly, deepening to the NW. 2 upflows are proposed at depth: major liquid-dominated upflow in the NW and a secondary, vapour-dominated upflow in the SE. Abstract: The Ohaaki Geothermal Field is a high temperature (300 °C) geothermal field located in the Taupo Volcanic Zone of New Zealand. Exploration for power development began in the 1960s, and by 1988 exploration results had led to the commissioning of a 110 MWe power station, which remains operating today. Drilling results from more than 70 wells and introduction of new technologies such as magnetotellurics (MT) and 3-D modelling, have largely contributed to an improved understanding of the deep geothermal resource. In this paper geological evidence (stratigraphy, structure and hydrothermal alteration) is reviewed, in conjunction with fluid geochemistry, reservoir characteristics (temperature, pressure and permeability distribution) and geophysical data (resistivity and gravity), to refine the conceptual model of the Ohaaki geothermal system. The bulk of the high-temperature reservoir is hosted in a volcaniclastic sequence capped between the shallow Huka Falls Formation and the deeper greywacke basement. The deep liquid reservoir across the West and East Banks is proposed to result from mixing of two end-members: a major liquid upflow in the northwest, and a secondary upflow in the southeast with a greater contribution of magmatic volatiles. These deep fluids rise to shallower depth where they undergo various degrees of boiling, dilution and cooling with shallow steam-heated groundwater.